2010
DOI: 10.1016/j.bpj.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Acetylcholine Receptor-Channel Agonist-Binding Sites with the Gate

Abstract: The gating isomerization of neuromuscular acetylcholine receptors links the rearrangements of atoms at two transmitter-binding sites with those at a distant gate region in the pore. To explore the mechanism of this reversible process, we estimated the gating rate and equilibrium constants for receptors with point mutations of alpha-subunit residues located between the binding sites and the membrane domain (N95, A96, Y127, and I49). The maximum energy change caused by a side-chain substitution at alphaA96 was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…5). The ␣1 Ϫ26Ј -␣1 19Ј coupling energy is well within the range for a significant interaction between residues in pLGICs during activation (39,40,44) and between ligand binding residues and ligand (45). We propose that this interaction represents one point of energy transfer along what is likely to be a broad reaction coordinate (broad corrugated activation barrier) as proposed by Auerbach for the related nAChR (40,46).…”
Section: Discussionsupporting
confidence: 67%
“…5). The ␣1 Ϫ26Ј -␣1 19Ј coupling energy is well within the range for a significant interaction between residues in pLGICs during activation (39,40,44) and between ligand binding residues and ligand (45). We propose that this interaction represents one point of energy transfer along what is likely to be a broad reaction coordinate (broad corrugated activation barrier) as proposed by Auerbach for the related nAChR (40,46).…”
Section: Discussionsupporting
confidence: 67%
“…Mutation of either of these residues alters GABA-mediated current responses, suggesting that this salt bridge is important for linking the binding site to loop 2 in the gating interface (41). Consistent with this idea, recent work from Cadugan and Auerbach (16) has shown that ␣A96 (loop A) and ␣I49 (loop 2) in the mouse nAChR, which are aligned to ␤K102 and ␤D56 of the GABA A R, respectively, are energetically coupled.…”
Section: Discussionmentioning
confidence: 74%
“…1) and is in an ideal position to propagate initial binding site movements to gating movements in the channel domain. Consistent with this idea, molecular dynamic simulations of the nAChR identified motions in the ␤4-␤5 linker that were correlated with motions in loops 2, 7, and M2-M3 near the extracellular mouth of the channel (14), and mutations in the nAChR ␣-subunit ␤4-␤5 linker alter channel gating (15,16). Based on the crystal structures of the nAChR ␣-subunit extracellular domain, AChBP, GLIC, ELIC, and the invertebrate glutamate-activated chloride channel (2,3,(5)(6)(7)(8), this linker region spans each subunit and is relatively unstructured.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The Ala and Asn substitutions had the largest effect and decreased E 2 by ϳ180-fold. The range energy for ⑀Arg 3Ј was ϳ3.1 kcal/mol, which is about the median value for two ␣-subunit mutations (10,30). The R/E plot for ⑀Arg 3Ј had a slope (⌽-value) of 0.73 Ϯ 0.06 (Fig.…”
Section: Resultsmentioning
confidence: 90%